SMART FUEL LEVEL INDICATOR (International Journal of Engineering Sciences & Management Research, 2019)
In this digital world, fuel makers are very advanced. Now days, at many petrol pumps we get exact amount of fuel in our vehicle. In this project the existing fuel in gauge technique being used in automobiles. In operating principle of smart and traditional fuel gauge system are compare between two exiting technique base on cost, accuracy and performance. The elimination of float sensor is due to its low accuracy in fuel indication. In our project we have used ultrasonic sensor to display the results of fuel level indication. In this experimental method analysis of our project yielded us satisfactory results over the conventional methods.